2008
DOI: 10.2304/rcie.2008.3.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Review: Constructing the Identity of Comparative Education

Abstract: The aim of this article is the explication of the identity of Comparative Education and a critical reflection thereon, by means of a journal analysis of articles published in the Comparative Education Review during the first 50 years of its existence. The 1157 articles were analyzed under the following rubrics: levels of analysis of articles; number of units covered by articles; geographical area which articles deal with authors: numbers, countries and institutional affiliation; research methods; paradigmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 39 publications
(27 reference statements)
1
19
0
1
Order By: Relevance
“…are most common in specific CIE journals (e.g. Foster, Addy, and Samoff, 2012;Koehl, 1977;Wolhuter, 2008). Through this type of research, scholars have been able to come to similar conclusions about the nature of the field and its genetic makeup over time:…”
Section: Nature Of the Fieldmentioning
confidence: 96%
See 1 more Smart Citation
“…are most common in specific CIE journals (e.g. Foster, Addy, and Samoff, 2012;Koehl, 1977;Wolhuter, 2008). Through this type of research, scholars have been able to come to similar conclusions about the nature of the field and its genetic makeup over time:…”
Section: Nature Of the Fieldmentioning
confidence: 96%
“…He created a framework of nine rubrics for categorisation, and though individual thematic percentages were not provided, he did present detailed percentage information on the three main thematic groupings: shaping forces; facets of the educational system; and effects of education (Wolhuter, 2008). From these findings, he determined that those forces shaping and influencing education were more often studied than themes taking place within educational institutions per se (Wolhuter, 2008). His most significant conclusion was that the field is experiencing "two equally strong trends -a remarkable resilience/constancy amid a broadening" (Wolhuter, 2008, p. 340).…”
Section: Journal Content Analysesmentioning
confidence: 99%
“…Southeast Asia has been a relatively popular region among Japanese comparative education scholars for some decades, but Africa, South and West Asia, the Arab region, and Latin America were not. Compared to that, Wolhuter's (2008) analysis of articles in CER from 1957 to 2006 demonstrates that Asia and Sub-Saharan Africa have constantly been the focus of articles together with North America and Western Europe. It is noteworthy that Africa and Asia have been well represented from the first volume of CER (Wolhuter 2008, 328;Foster et al 2012, 712).…”
Section: Journal Of Comparative Education (Jce-t Hereafter) Publishedmentioning
confidence: 99%
“…First, I will compare publication trends in the journals of JCES and CIES, namely, CE-J and Comparative Education Review (CER hereafter). Then, the paper will turn to the comparison of trends between CE-J and Comparative Education Review (CER-C hereafter) of the Chinese Comparative Education Society (CCES), To contrast the research trends observed through the articles published in CE-J and CER, I relied on the analysis provided by Charl C. Wolhuter (2008). Wolhuter classified 1,157 articles appearing in CER, from the first volume in 1957 to 2006.…”
Section: Convergence With and Divergence From The Patterns In North Amentioning
confidence: 99%
“…the objectives, methods and curricula of Comparative education courses) has been virtually absent from the Comparative education research agenda (cf. Wolhuter, 2008). Thus, while comparative education is a prolific field, the part of its existence most pivotal to its future, namely the teaching of Comparative education, has eluded the attention of scholars in the field.…”
Section: The Presence Of Comparative Education At Universitiesmentioning
confidence: 99%